Permutations of Theory – Open Channels then and now - Holger Briel (KOME: An International Journal of Pure Communication Inquiry)
This paper presents the case of Public Access Channels (or OpenChannels) in a changing media climate. The author argues that Public Access Television was a forerunner of today’s internet, as it honed viewers’ interactive capabilities by involving them in the production processes of video material. It was a clear remit of these stations to train individuals to use visual media and become their own directors. Thus, it was argued, they would be able to better understand traditional visual media and would not continue to powerlessly live under their spell. Also, it would empower them by allowing their own content to be screened. With the advent of the internet, many of the above beliefs were realised. And, consequently, Public Access Television underwent a crisis, as its target audience migrated to online media, such as YouTube and others. However,its training remit is still valid today and, perhaps, more so than ever before as much more visual material is pushed onto viewers. Once stations realize the potential of the internet to its fullest (e.g. the need for training and the availability of unlimited channels), they stand a good chance to once again become an important player in video education and local engagement.